Morning chronotype and digestive tract cancers: Mendelian randomization study. Issue 4 (22nd September 2022) - Yuan, Shuai; Mason, Amy M.; Titova, Olga E.; Vithayathil, Mathew; Kar, Siddhartha; Chen, Jie; Li, Xue; Burgess, Stephen; Larsson, Susanna C.
Abstract: Morning chronotype has been associated with a reduced risk of prostate and breast cancer. However, few studies have examined whether chronotype is associated with digestive tract cancer risk. We conducted a Mendelian randomization (MR) study to assess the associations of chronotype with major digestive tract cancers. A total of 317 independent genetic variants associated with chronotype at the genome‐wide significance level ( P  < 5 × 10 −8 ) were used as instrumental variables from a genome‐wide meta‐analysis of 449 734 individuals. Summary‐level data on overall and six digestive tract cancers, including esophageal, stomach, liver, biliary tract, pancreatic and colorectal cancers, were obtained from the UK Biobank (11 952 cases) and FinnGen (7638 cases) study. Genetic liability to morning chronotype was associated with reduced risk of overall digestive tract cancer and cancers of stomach, biliary tract and colorectum in UK Biobank. The associations for the overall digestive tract, stomach and colorectal cancers were directionally replicated in FinnGen. In the meta‐analysis of the two sources, genetic liability to morning chronotype was associated with a decreased risk of overall digestive tract cancer (odds ratio [OR] 0.94, 95% confidence interval [CI]: 0.90‐0.98), stomach cancer (OR 0.84, 95% CI: 0.73‐0.97) and colorectal cancer (OR 0.92, 95% CI: 0.87‐0.98), but not with the other studied cancers. The associations were consistent in multivariable MR analysis with adjustment for genetically predicted sleep duration, short sleep, insomnia and body mass index. The study provided MR evidence of inverse associations of morning chronotype with digestive tract cancer, particularly stomach and colorectal cancers. Abstract : What's new? Cancers of the digestive tract are associated with various traditional risk factors, including smoking and obesity. A possible novel risk factor may be chronotype, an individual's natural tendency to sleep at a particular time. In our study, the authors assessed potential associations between digestive tract cancers and chronotype using Mendelian randomization analysis of UK Biobank and FinnGen study data. Overall risk of digestive tract cancer, stomach cancer and colorectal cancer was found to be inversely associated with genetic liability to morning chronotype. Analyses further indicate that the associations are independent of sleep duration, short sleep, insomnia and body mass index.